2017
DOI: 10.1136/bmjopen-2016-015284
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone therapy in hypogonadal men: a systematic review and network meta-analysis

Abstract: ObjectiveTo assess the relative effects of individual testosterone products among hypogonadal men.DesignSystematic review and network meta-analysis.MethodsWe searched MEDLINE, Embase, Cochrane CENTRAL, and grey literature (25 May 2017) for randomised-controlled trials (RCTs) and non-randomised studies (NRS) that involved hypogonadal men given testosterone replacement therapy (TRT) for ≥3 months. Comparators were placebo, another TRT, or the same product at a different dose. Outcomes were quality of life, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Hypogonadism is also related to low testosterone levels. 25 Men with bilateral and unilateral UDT had lower testosterone levels than men without UDT, even though they were all within the normal range. Hypogonadism results from abnormal amounts of physiological concentrations of testosterone due to the pathological functioning of the testes, which produce testosterone which has an essential role in male reproductive and sexual function, metabolism, and body composition.…”
Section: Effect Of Udt On Hypogonadismmentioning
confidence: 84%
“…Hypogonadism is also related to low testosterone levels. 25 Men with bilateral and unilateral UDT had lower testosterone levels than men without UDT, even though they were all within the normal range. Hypogonadism results from abnormal amounts of physiological concentrations of testosterone due to the pathological functioning of the testes, which produce testosterone which has an essential role in male reproductive and sexual function, metabolism, and body composition.…”
Section: Effect Of Udt On Hypogonadismmentioning
confidence: 84%
“…In a setting where only patients with hypogonadism were considered, Elliott and coll. evaluated the effect of TRT on many outcomes, including quality of life, depression, sexual function, metabolic and adverse events ( 128 ). As far as depressive symptoms are concerned, the analysis of 12 RCTs (852 patients) showed that, compared with placebo, treatment with any TRT improved depression.…”
Section: Effects Of Testosterone Replacement Therapy On Depressionmentioning
confidence: 99%
“…Testosterone is essential for the maintenance of muscle mass, sex drive, bone density, and fertility of men. Testosterone deficiency (TD) could be caused by various conditions, and testosterone is widely used for testosterone replacement therapy (TRT), to restore the testosterone level of men with hypogonadism or with low testosterone levels (low-T), which is considered as a safe and effective hormone supplement ( Elliott et al, 2017 ; Bhasin et al, 2018 ) and treatment for certain types of cancers, such as hormone therapy for prostate cancer ( Bhasin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Bhasin et al (2022 ) excised a study including 6,000 subjects and determined that TT in middle-aged and older men with hypogonadism was with or at increased risk of CV diseases. On the contrary, there were other publications that pointed out that TT has no effect on MACEs or that it even presented some beneficial effects ( Wang et al, 2011 ; Baillargeon et al, 2015 ; Cheetham et al, 2017 ), including statements that TT is associated with a decrease in atherosclerosis, hypertension, intima–media thickness of carotid arteries, insulin resistance, and mortality in men due to all causes ( Morgentaler et al, 2015 ) and no short-term increased risk of adverse events (AEs) is observed among subjects with hypogonadism ( Elliott et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%